أخلاقيات العمل الصحفي في المؤسسات الإعلامية الجزائرية دراسة ميدانية على الصحف الصادرة بمدينة وهران - بقدوري عز الدين (My University, 2017)
This study intends to define the deontology of the journalistic job in the Algerian communication enterprises. This survey concerns primarily the papers published in the west of the country, Oran, and the journalists respect of the deontology in the wilayats mentioned above. Without forgetting that this job, in the time assigned to, goes in pair with the emergence of the organic law of information in Algeria in 2012, where articles and decrees have been used to adjust the journalistic work, and especially make the job deontology known by reminding the rights and duties, without affecting the freedom of expression and opinion and citizen s right to the accurate, transparent and pragmatic news which respects the universal rules that organize and adjust the activity of journalism. Hence, this job constitution has raised some restrictions and obstacles which prevent the journalist to get the information from the source. Bearing in mind that the various political and social changes that taken place in the country have set free the journalist to tackle some issues which used to be regarded as “ taboo” before 1989. Now, we should emphasize that the lack of professionalism and experience with some colleagues has caused enough trouble among which we can mention the lack of credibility of the media. Thus, the deontology code has become necessary to prevent certain usurpations such as the transgression of the people s private life and institutions. Our survey, hereby, has been based on a global investigation because of the easiness of access to the individuals of the society, estimated on 131 items distributed on 26 titles -13 papers in Arabic and 13 in French and, we handed out a form to all the journalists of the wilayat of Oran. The individual carrying the survey has gone so far as to organize interviews with editors of six newspapers “El Masaa”, “El Djazair Sahafa”, La Tribune Des Lecteurs”, “El Wassel” and “El Djemhouria” as we deliberately asked 42 questions to collect as much data related to our issue. The conclusions of the survey got the following points mentioned bellow; *The survey has shown that the concerned informants have never complained about pressure neither in their enterprises nor outside, which confirms somehow the freedom of expression of the journalists in Western Algeria. *The same survey concluded that 27.92% of the informants suffer their colleague’s competition in one hand the shock of the sexist consideration in the other hand. *Most of the informants accept the deontology charter with reservation for the fact that they have not taken part in making it. *Most of the journalists interviewed affirm that they keep up to the deontology charter with respect to the reader who wants the news to be accurate and right all over the country. *All the journalists agree that the competition does not allow the deontology rules usurpation. *39.7% of the informants confirm the existence of the deontology charter inside their enterprises as a permanent working means. *The survey has revealed that the decay of the written press has made some journalists endure many problems, especially the access to divers sources of information.